OPTIMIZING THE ROLE OF PRINCIPAL IN MANAGING FACILITIES AND INFRASTRUCTURE TO IMPROVE THE QUALITY OF ELEMENTARY EDUCATION - Azzahra, Devina; Nukman, Muhamad (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
In improving the quality of education, the role of the principal is very much needed to manage facilities and infrastructure. However, in reality there are still schools whose facilities and infrastructure are inadequate. So the role of the principal is very much needed in managing facilities and infrastructure in schools. The purpose of this study is to gain an understanding of the role of the principal in managing facilities and infrastructure towards the quality of education at SD Negeri 8 Pekanbaru. This study uses a qualitative research type. The subjects in this study were the principal and teachers of SD Negeri 8 Pekanbaru. Data collection techniques and instruments used observation, interview and documentation techniques. The validity test of the data in this study used the triangulation technique of source data, techniques and time. The data analysis method used is in accordance with the theory of Miles and Huberman which has stages, namely data reduction, data presentation and drawing conclusions. The results of the study showed that the principal of SD Negeri 8 Pekanbaru plays a very important role in managing facilities and infrastructure towards the quality of education. The principal at Pekanbaru 8th State Elementary School plays a role in planning the budget for procurement, construction, maintenance and repair of school facilities, distribution and making an inventory of procurement of facilities and infrastructure and providing a warehouse for storage and reporting items that are written off.